Cross-Talk Between Gut Microbiota and Adipose Tissues in Obesity and Related Metabolic Diseases - Wu, Dan; Wang, Huiying; Xie, Lijun; Hu, Fang (Frontiers in Endocrinology, 2022)
The prevalence of obesity and associated diseases has become a major global health problem. Adipose tissues play critical roles in whole-body homeostasis. The gut microbiota has been recognized as an important environmental factor in the maintenance of energy homeostasis and host immunity. A growing body of evidence suggests that the gut microbiota contributes to host metabolism through communication with adipose tissues. It modulates energy expenditure and alleviates obesity by promoting energy expenditure, but it also produces specific metabolites and structural components that may act as the central factors in the pathogenesis of inflammation, insulin resistant and obesity. Understanding the relationship between gut microbiota and adipose tissues may provide potential intervention strategies to treat obesity and associated diseases. In this review, we focus on recent advances of the gut microbiota and its actions on adipose tissues, and highlight mutual actions of the gut microbiota and adipose tissue with each other in the regulation of energy metabolism.